Chapter Unending Wandering: visions of mobility in Zou Taofen's Italy - Castorina, Miriam (Studi e saggi, 2023)
This paper focuses on visions and representations of Italy that emerge from the travel writings and narrative intersections of Sino-Italian mobilities. Taking its primary example from the travels of Zou Taofen (1895-1944), who enshrined his memories of Italy in Pingzong jiyu 萍踪寄语 (Messages from an unending wandering) while exiled from China, this critical exploration of mobility traces the spread of ideas between the Italian Peninsula and the Republic of China. Zou's new and original visions of Italy reached a broad readership during the republican period, spreading widely and making Zou a "central figure of the New Culture era." Despite his place as one of the most successful and influential journalists in the history of the Republic of China, Zou has not yet "received his full due" (Mitter 2004, 55).